Maize–legume strip cropping effect on productivity, income, and income risk of farmers in northern Ghana - Rahman, N.A.; Larbi, Asamoah; Kotu, Bekele Hundie; Asante, M.O.; Akakpo, D.B.; Bedi, S.M.; Hoeschle‐Zeledon, I. (Wiley, 2021)
Maize (Zea mays L.)–legume intercropping is common cropping system among smallholder farmers in West Africa. However, little is known about the income risk reduction associated with maize–legume strip cropping in West Africa. A 3‐yr study was conducted in Upper West and Northern regions of Ghana to determine the effect of maize–legume strip cropping on productivity, income, and income risk using a randomized complete block design with five replications in each region. Seven treatments were used: sole crops of maize (M) cowpea [Vigna unguiculata (L.) Walp.] (C) and groundnut (Arachis hypogaea L.) (G), a combination of two rows of M and two rows of legumes (L) (2M:2C and 2M:2G), and two rows of M and four rows of L (2M:4C and 2M:4G). Maize–legume strip cropping options (2M:2L and 2M:4L) on the average saved 90–100% of agricultural land, significantly increased income by about threefold, and reduced risk of operating at a financial loss by 75% compared with sole cropping. Smallholder farmers, especially sole legume cropping farmers in the Guinea savanna of northern Ghana and similar agro‐ecologies in West Africa, could adopt maize–legume strip cropping systems (2M:4L or 2M:2L) to mitigate production risk and increase financial return.